What Makes Antibodies Against G Protein-Coupled Receptors so Special? A Novel Concept to Understand Chronic Diseases - Riemekasten, Gabriela; Petersen, Frank; Heidecke, Harald (Frontiers in Immunology, 2020)
Expressions of G protein-coupled receptors (GPCR) on immune and tissue resident cells are the consequence of the cellular environment, which is highly variable. As discussed here, antibodies directed to GPCR (GPCR abs), their levels and correlations to other abs, serve as biomarkers for various diseases. They also could reflect the individual interplay between the environment and the immune system. Thus, GPCR abs could display pathogenic chronic conditions and could help to identify disease-related pathways. Moreover, by acting as ligands to their corresponding receptors, GPCR abs modulate autoimmune as well as non-autoimmune diseases. This article introduces GPCR abs as drivers for diseases by their capability to induce a specific signalling and by determining immune cell homeostasis. The identification of the individual GPCR ab function is challenging but might be pivotal in the comprehension of the aetiology of diseases. This, hopefully, will lead to the identification of novel therapeutic strategies. This article provides an overview about concepts and recent developments in research. Accordingly, GPCR abs could represent ideal candidates for precision medicine. Here, we introduce the term antibodiom to cover the network of abs with GPCR abs as prominent players.